A view on countries’ tourism logos, slogans, contents and figural characteristics within the concept of country identity - Zeybek, Burcu; Gül Ünlü, Derya (Information & Media, 2017)
Competition increases in parallel with the rise of globalisation and brands are being used to market a product and reach large masses of people. A brand is a promotion tool which distinguishes one product from another. A brand is defined as a name, term, sign, symbol, or design, or a combination of them intended to identify the goods and services of one seller or group of sellers and to differentiate them from those of the competition. Branding is the process of a firm introducing a product or a service to consumers as a brand and infusing the consumers with them or making the consumers more dependant on an existing brand. This process requires many decisions to be taken and strategies to be adopted and followed. The very first aim in branding process is getting known. To achieve this, firms need to promote a brand or service using advertisements or other activities. The field of practice of branding is not limited to products and services but includes individuals, ideas, facts and places (country, region, city etc.). Thus, countries, cities and even nations aim at branding and promote different various strategies this way. The importance of a country brand has gradually increased with the effect of changing social, cultural and economic developments, those as a result of globalisation. Countries find the opportunity to present themselves better, and create a better image about themselves in a global public opinion. Today, the identity and image creation process has significant functions ranging from advertising and public relations to mass media and popular culture, politics to fashion and sales, and the whole country and the presentation of a country when considered in general sense. Therefore, like organisations, countries began taking place in the global market and implementing various communication strategies to highlight their historical, geographical and cultural characteristics. That countries can promote themselves using efficient policies will also enable their cities and brands to differentiate from others and become competitive and this will provide those countries with more global recognition and branding. To put it differently, country branding makes it easier, faster and more reliable for one to prefer and decide which country to visit, what to purchase in relation to a country, arranging a business trip and collecting impressions about a country. One of the most important actions that must be taken by the countries to promote their cultural elements and values is to create visual identity. Country identity and image is achieved primarily through designing a good logo, which is also the basis of visual identity studies. In addition to symbols such as a flag and an emblem, each country has a promotional tourism logo, which reflects their visual image. The main subject of this research is reviewing tourism logos of countries in the context of country identity. A categorical content analysis technique will be applied in the research methodologically, and the research is limited to 47 European Council member countries. From this point of view, the logos of countries will be analysed in terms of their content, aesthetic, originality, historical, touristic, architectural and cultural characteristics, and the importance of logos in the process of creating country identity will be addressed.
Keywords: country identity; visual identity; country branding